Implementation of a Budo group therapy for psychiatric in- and outpatients: a feasibility study - Singh, Jasprit; Jawhari, Karl; Jaffé, Mariela; Imfeld, Lukas; Rabenschlag, Franziska; Moeller, Julian; Nienaber, André; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2024)
Physical exercise has been shown to have numerous health benefits on co-morbid somatic conditions in psychiatry and can also enhance mental health. Thus, it is not difficult to recommend physical training programs as part of an integrated and holistic treatment approach for mental health disorders. However, getting patients to participate and keeping them engaged is a major challenge. Programs based on martial arts training could be interventions improving physical and mental health with higher attachment rates. The structured discipline, holistic approach integrating physical and mental elements, and empowering activities, may explain higher participant attachment rates. Thus, the main objective of this feasibility study is to describe a newly established group therapy program incorporating interventions from martial arts training with its physical and philosophical parts including mindfulness and breath work. During the 14-month study period from April 2021 to May 2022, a Budo group therapy was used by 215 individual persons with a total of 725 group therapy participations. Retention in the program was good across all settings and very good for persons who participated as outpatients. The mean age of the participants was 33.5 years with a range from 14 to 69 years of age, and about 41% of the participants were female. The therapy program was able to address patients over the whole spectrum of psychiatric diagnoses. Satisfaction and motivation were uniformly self-reported as very good. Patients self-reported improved mental and physical health after participating in a Budo session compared to pre-session. Budo group therapy thus can be seen as a feasible, well-accepted and promising new transdiagnostic treatment approach, combining physical activation with resilience enhancement. With minimal contraindications, a broad spectrum of individuals seeking mental health support can engage in this group therapy.